Diferenciação craniana infraespecífica em Proechimys iheringi Thomas e Proechimys dimidiatus (Guenter) (Mammalia: Rodentia: Echimyidae) - Pessôa, Leila Maria (1989)
The genus Proechimys is one of the most diversified groups among the neotropical rodents, and also one of the most poorly understood. This genus was subdivided by Moojen (1948) into two subgenera , namely the subgenus Proechimys and the subgenus Trinomys on the basis of the length of the main fold in the molariform teeth. The objective of this study was to analyze variation within populations (sexual dimorphism and age variation) and infraspecific differentiation in two species of the subgenus Trinomys: Proechimys (Trinomys) iheringi with six described subspecies and Proechimys (Trinomys) dimidatus. The latter species is considered to be monotypic . Thirteen cranial measurements were taken from three populations of P. iheringi and four populations of P. dimidiatus. The specimens examined in this study are housed at the Museu Nacional, RJ. Sexual dimorphism was analyzed in three populations of P. dimidiatus, and males were found to be always larger than females, although few characters were statistically significant. This analysis also showed that sexual dimorphism varies geographically, Analysis of variance showed that populations of P. iheringi differed significantly (P < 0.05) in all 13 cranial characters, Discriminant function analysis correctly classified most individuals of P. iheringi to their groups defined 'a priori', Canonical variates analysis discriminated the populations from Bahia and Espírito Santo along canonical variate I, whereas canonical variate II separated almost completely the populations from Rio de Janeiro and Espírito Santo. The three populations were ordinated along a cline of increasing cranial size similar to that found by Moojen (1948) for dental characters. Mantel's Z test deaonstrated a significant posftive correlation between aorphologic and geographic distance among the E, iherinqi populations. ln P. diaidiatus 10 cranial characters differed significantly (P < 0.05) by an analysis of variance, Discriaination between populations of P. diaidiatus froa Teresbpolis and Ilha Grande was coapiete (100%), whereas populations from Tijuca and Parati had 92% and 76% of correct classification, respectively. The populations from Tijuca and Teresópolis were unambiguously discriainated along canonical variate I, whereas the population from Ilha Grande was coapletely separated from the population from Teresópolis and Tijuca along canonical variate II. The population from Parati is morphologically diverse and overlaps aorphologically with the reaaining populations. A nonsignificant correlation was found for geographic and morphologic distance for P. dimidiatus. our results corroborate Moojen's findings on geographic differentiation for P. iheringi. on the other hand, we detected geographic variation for populations of P. ditidiatus not reported by Moojen (1948), The pattern of differentiation in the two species appear to be different, since variation in P. iherinqi is clinal whereas there seeas to be no geographic pattern to the variation observed for P. diaidiatus.